APPLICATION OF THE ANALYTIC HIERARCHY PROCESS IN IDENTIFYING TALENT OF KARATE ATHLETES AGED 6-12 YEARS - Fauzan, Ananda Ammar; Rusdiana, Agus; Haryono, Tono; Hidayat, Iwa Ikhwan; Kurniawan, Tian; Palgunadhi, Finaldhi (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Talent identification in young karate athletes is a crucial phase for optimizing targeted achievement development programs. This study aims to apply the Analytic Hierarchy Process (AHP) method to establish a priority hierarchy of criteria and sub-criteria in talent development for karate athletes aged 6–12 in West Java Province. This study involved 22 karate experts, consisting of coaches and accomplished athletes, to assess the weighting of three main criteria:antropometer,biomotor, andsomatotype, which were further broken down into 14 sub-criteria. Quantitative data analysis was performed using Expert Choice 11 software. The results of the analysis show that in the domainantropometer, height (0.173) is the indicator with the highest priority. In the biomotor domain, agility (0.225) shows the highest weight value compared to strength, endurance, speed, and flexibility. Meanwhile, in the domainsomatotype, body typologymesomorf(0.418) ranks as the top priority, followed by endomorph (0.379) and ectomorph (0.202). Comprehensively, the criteriasomatotype(34%) made the most significant contribution to the overall talent identification model, followed by biomotor andantropometer.These findings affirm the AHP's capability in developing a systematic and objective talent identification model, which can serve as a strategic guideline for coaches in the selection and development process of potential karate athletes from an early age.